Evaluation of Hemolysis as a Severe Feature of Preeclampsia. Issue 2 (August 2018) - Burwick, Richard M.; Rincon, Monica; Beeraka, Sridivya S.; Gupta, Megha; Feinberg, Bruce B.
Abstract : Hemolysis predisposes to adverse pregnancy outcomes. Yet, there are limited data on hemolysis in hypertensive disorders of pregnancy other than hemolysis, elevated liver enzymes, and low platelet count syndrome. To evaluate the prevalence and impact of hemolysis in hypertensive disorders of pregnancy, we performed a retrospective cohort study at a single center (October 2013–May 2017), among women screened for hemolysis using lactate dehydrogenase (LDH) levels. We compared LDH levels by hypertensive disorder (chronic hypertension, gestational hypertension, preeclampsia, and preeclampsia with severe features) and evaluated impact on adverse pregnancy outcomes. Data were analyzed by χ 2 or t test, ANOVA, test of medians, and logistic regression. Among 8645 deliveries, 1188 (13.7%) had a hypertensive disorder. Of these, 812 (68.4%) had LDH measurement before delivery: chronic hypertension (n=152); gestational hypertension (n=209); preeclampsia (n=216); and preeclampsia with severe features (n=235). LDH ≥400 U/L (≥1.6× normal) was more common in preeclampsia with severe features compared with other hypertensive disorders of pregnancy (9.8% versus 2.3%; P <0.001); adjusted odds ratio 4.52 (95% confidence interval, 2.2–9.2; P <0.001). LDH ≥400 U/L was associated with adverse maternal outcomes (41.7% versus 15.3%; P <0.001), adjusted odds ratio 3.05 (95% confidence interval, 1.4–6.7; P =0.006), and adverse neonatal outcomes (eg, preterm birth 59.4% versus 22.5%; P <0.001). We find that elevated LDH levels are associated with adverse maternal and neonatal outcomes in hypertension and preeclampsia, independent of hemolysis, elevated liver enzymes, and low platelet count syndrome. Therefore, elevated LDH levels (≥1.6× normal or ≥400 U/L) may be considered a severe feature of preeclampsia. Abstract : Supplemental Digital Content is available in the text.